Four new species of Herpothallon (Arthoniaceae, Arthoniales, Arthoniomycetes, Ascomycota) from China - Chen, Pengfei; Liu, Linlin; Xie, Congmiao; Zhang, Lulu (Phytotaxa, 2022)
Four new species of Herpothallon: H. capilliferum, H. polyisidiatum, H. subglobosum and H. viridi-isidiatum are described from southern China. Detailed taxonomic descriptions, ecological and chemical characters, and illustrations are provided for the new species. A key to all known Chinese Herpothallon species is also provided.